Impact of Maternal High-Fat Induced Obesity on Offspring's Liver Transcriptome. (14th June 2022) - Ortega, Edwin; Guo, Weimin; Li, Lijun; Wu, Dayong; Meydani, Simin
Abstract: Objectives: Epidemiological studies suggest that parental obesity is associated with an increased risk of childhood obesity. We previously demonstrated that maternal obesity had a transgenerational impact on offspring body weight; however, this effect was sex specific, with male offspring being more susceptible to weight gain in comparison to their female counterparts. To elucidate the potential underlying mechanisms for this observation we characterized the offspring's liver transcriptome. Methods: To determine the potential mechanisms by which maternal obesity could differentially impact the offspring's susceptibility to weight gain we characterized the offspring's liver transcriptome (n = 6–8/sex). The quality of the liver transcriptome was assessed by FastQC. The reads were aligned and mapped using the Bowtie R package. Gene expression was normalized by FPKM using the Cufflinks R package. Differential gene expression and gene set enrichment analyses (GSEA) were performed using the DEseq and Limma R packages, respectively. An FDR adjusted p-value (q-value) < 0.05 was considered statistically significant. Results: Differential analysis demonstrated that 2275 transcripts were differentially expressed between male and female offspring (q < 0.05). Of those 2275, 265 mRNAs were had a 1.5-fold higher (154) or lower (111) level of expression in the male offspring in comparison to the female offspring. Using the Gene Ontology and KEGG database, GSEA was performed using a set of 237 mRNAs that met our pre-selected criteria (q < 0.05, ±1.5-fold difference in gene expression level, had an Entrezgene ID). GSEA revealed that the top molecular function and biological process enriched in our unique gene set was, unsurprisingly, steroid hormone synthesis. Notably, GSEA further revealed significant differences in lipid/lipid oxidation metabolism, arachidonic and eicosanoid metabolism, cytochrome P450 metabolism, and immune system responses. Conclusions: Our study suggests that the expression of genes involved in a variety of biological processes differ between male and female offspring born to obese mothers. Differences in these pathways may underlie the sex-driven difference in body weight gain. Funding Sources: This material is based upon work supported by the U.S. Department of Agriculture – Agricultural Research Service, Agreement No. 58-1950-4-003.